Rahinah wins US 'fight' - Shah, Aliza; Shahrudin, Hani Shamira (2014)
After Dr Rahinah Ibrahim's nine-year exhaustive battle to strike her name off the United States Department of Homeland Security's terrorist watch list, the architecture professor, who won her case on Tuesday, has emerged unscathed.